Pigtail Catheter versus Large Bore Chest Tube for the Management of Spontaneous Pneumothorax in Children: A Retrospective Study - Weiss, Tal; Dreznik, Yael; Kravarusic, Dragan (European Journal of Pediatric Surgery, 2023)
Introduction Pigtail catheter (PGC) insertion due to spontaneous pneumothorax (SPT) in the pediatric population has increased markedly in the last years. However, only few studies examined its efficacy in terms of length of hospitalization, rate of complications, and especially pain management comparing to large bore catheter (LBC) insertion. We sought to compare analgetic drug consumption, efficacy, and complication rate between PGC and LBC in children with SPT.Materials and Methods This is a single-center retrospective study of pediatric patients that were admitted to the Schneider Children's Medical Center between 2013 and 2021 with a diagnosis of SPT. The following data were collected: type of drainage (PGC or LBC), duration of drainage, length of hospitalization, number of X-rays, complication rate, surgery during hospitalization, readmission due to SPT, and pain management.Results Seventeen PGC and 23 LBC were inserted in our study. No differences were noted in terms of hospitalization length, tube reposition or replacement, and recurrence of SPT between the groups. Patients with PGC underwent less X-rays comparing to the LBC group (3 X-rays vs. 5, median, p < 0.005). Oral analgesic use in terms of length of therapy was significantly lower in the PGC group than in the LBC group (1 vs. 3+ days, median, p < 0.05). There was no major complication in this cohort.Conclusion PGC is an effective, safe, and less painful alternative compared with a LBC for the drainage of SPT in children.
Keywords: spontaneous pneumothorax; pigtail catheter; large bore chest tube; pediatric